Early psychological intervention in adult patients after hospitalization during COVID-19 pandemia. A single center observational study - Lazzaroni, Elisa; Tosi, Davide; Pontiggia, Silvia; Ermolli, Riccardo; Borghesi, Luca; Rigamonti, Vittorio; Frisone, Enrico; Piconi, Stefania (Frontiers in Psychology, 2022)
The coronavirus disease 2019 pandemic has represented an individual and collective trauma with an impact on mental health. COVID-19 survivors need to be screened for psychological distress regularly for timely intervention. After March 2020, an outpatients clinic for follow up of discharged COVID-19 patients was set up at Infectious Diseases Department of the Hospital of Lecco, Italy. Blood exams, specialistic visits were performed for each patients and IES-R and BDI scales were dispensed. 523 patients were referred to the clinic; 93 of them resulted positive at IES-R and/or BDI self-report and 58 agreed to have early interviews with psychologist specialist. Patients could receive only a short psychoeducation/psychological support intervention or in addition to the same, even a specific trauma-focused psychotherapeutic intervention with EMDR where clinically indicated. IES-R e BDI were administered pre- and post-intervention. The results show that the average of the post-traumatic stress scores detected at IES-R is above the clinical cut-off for the entire sample. There is an overall change in the decrease in mean scores on the IES and BDI scales before and after psychological intervention. Among the patients for whom psychopharmacological therapy was also necessary, those who had COVID-mourning in family improved the most at IES-R scale post- intervention. With respect to EMDR treatment, there is a significant improvement in depressive symptoms noticed at BDI for male patients who have received neither psychotropic drugs nor CPAP. Being hospitalized for coronavirus has a significant impact on the patient’s mental health and it is a priority to arrange early screening to intercept psychological distress and give it an early response.